Impact of climate change on the kelp Laminaria digitata – simulated Arctic winter warming - Moritz Trautmann; Inka Bartsch; Margot Bligh; Hagen Buck-Wiese; Jan-Hendrik Hehemann; Sarina Niedzwiedz; Niklas Plag; Tifeng Shan; Kai Bischof; Nora Diehl (Frontiers in Marine Science, 2024)
The Arctic is seasonally exposed to long periods of low temperatures and complete darkness. Consequently, perennial primary producers have to apply strategies to maximize energy efficiency. Global warming is occurring in the Arctic faster than the rest of the globe. The highest amplitude of temperature rise occurs during Polar Night. To determine the stress resistance of the ecosystem-engineering kelp Laminaria digitata against Arctic winter warming, non-meristematic discs of adult sporophytes from Porsangerfjorden (Finnmark, Norway) were kept in total darkness at 0°C and 5°C over a period of three months. Physiological variables, namely maximum quantum yield of photosynthesis (F v /F m ) and dry weight, as well as underlying biochemical variables including pigments, storage carbohydrates, total carbon and total nitrogen were monitored throughout the experiment. Although all samples remained in generally good condition with F v /F m values above 0.6, L. digitata performed better at 0°C than at 5°C. Depletion of metabolic products resulted in a constant decrease of dry weight over time. A strong decrease in mannitol and laminarin was observed, with greater reductions at 5°C than at 0°C. However, the total carbon content did not change, indicating that the sporophytes were not suffering from “starvation stress” during the long period of darkness. A decline was also observed in the accessory pigments and the pool of xanthophyll cycle pigments, particularly at 5°C. Our results indicate that L. digitata has a more active metabolism, but a lower physiological and biochemical performance at higher temperatures in the Arctic winter. Obviously, L. digitata is well adapted to Arctic Polar Night conditions, regardless of having its distributional center at lower latitudes. Despite a reduced vitality at higher temperatures, a serious decline in Arctic populations of L. digitata due to winter warming is not expected for the near future.